River Connectivity is Crucial for Safeguarding Biodiversity but May be Socially Overlooked. Insights From Spanish University Students - Arboleya, Elena; Fernández, Sara; Clusa, Laura; Dopico, Eduardo; Garcia-Vazquez, Eva (Frontiers in Environmental Science, 2021)
The social value of natural aquatic ecosystems is very important to set management priorities. River connectivity is essential for the conservation of freshwater ecosystems because barriers alter both abiotic conditions and the biotic communities, compromising biodiversity; however, the appreciation of this river feature has been insufficiently considered in socio-environmental studies that are mainly focused on the acceptance of new dams. Here we used a willingness to pay approach to estimate the value of connectivity, autochthonous species, biodiversity, fish abundance and environmental quality in three groups of students of different educational background in Asturias (NW of Spain). As in other studies where they are more sensitive to environmental issues, educational sciences students would pay more to conserve and improve river conditions than students of other disciplines. Connectivity was the least valued river feature by students of educational and natural sciences, and the third (before biodiversity and fish abundance) by engineering students. We measured the same features on lowland reaches of four coastal rivers in the Bay of Biscay, and applied declared will amounts to model their appreciation. Differences between the ranks obtained from ecological features and students’ prioritization, and small differences between students of different disciplines in the gap between most and least preferred rivers arise from the model, indicating the importance to involve diverse stakeholder sectors in decisions about rivers. The importance of river connectivity in the conservation of local biodiversity, here reflected in significant correlation between damming and exotic species, should be explained to general public, perhaps through environmental campaigns.